2022
DOI: 10.3389/fpubh.2022.889870
|View full text |Cite
|
Sign up to set email alerts
|

Improving Patient Safety Culture During the COVID-19 Pandemic in Taiwan

Abstract: Background and AimPatient safety culture attitude is strongly linked to patient safety outcomes. Since the onset of the COVID-19 pandemic in early 2020, pandemic prevention has become the priority of hospital staff. However, few studies have explored the changes in patient safety culture among hospital staff that have occurred during the pandemic. The present study compared the safety attitudes, emotional exhaustion (EE), and work–life balance (WLB) of hospital staff in the early (2020) and late (2021) stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“… 90 Recently, a crisis response strategy has been proposed to positively change the safety climate attitudes after the pandemic. 91 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 90 Recently, a crisis response strategy has been proposed to positively change the safety climate attitudes after the pandemic. 91 …”
Section: Discussionmentioning
confidence: 99%
“…90 Recently, a crisis response strategy has been proposed to positively change the safety climate attitudes after the pandemic. 91 Although staffing shortages are a known issue in Latin America 92 the COVID-19 pandemic exacerbated it. 93 In this context, staffing issues-reported here as one of the worse scores (40.2% (CI 95% 36 to 44))-may also influence our results since the perception of patient safety has been related to the availability of appropriated staffing, 94 and it is essential for achieving more favourable PSC.…”
Section: Dimensions 'Requiring Improvements'mentioning
confidence: 99%
“…While the role of healthcare providers in delivering care and ensuring patient safety is widely acknowledged, it is equally important to recognize the significance of clinical managers in fostering a culture of safety at the organizational level [ 19 ]. Clinical managers play a vital role in fostering a positive patient safety culture and creating nonpunitive environments to promote patient safety [ 20 , 21 ]. Their leadership and managerial activities significantly influence medical staff adherence to hospital processes, particularly in areas such as teamwork and communication [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patient safety culture has gradually been attached importance by healthcare organizations around the world. Patient safety culture refers to employees' shared beliefs, attitudes, values, norms, and behavioral characteristics regarding patient safety and is considered an important component of hospital culture that is oriented towards patient safety (1,2). Studies indicated that healthcare institutions can have many positive outcomes if they are able to possess a good patient safety culture.…”
Section: Introductionmentioning
confidence: 99%